Rekacipta Tradisi Kue Bulan Pada Perkembangan Kontemporer Budaya Etnis Tionghoa di Bogor - Saputra, Nicko (Universitas Padjadjaran, 2025)
The moon cake tradition is an important cultural practice among the Chinese ethnic community, carried out to welcome the arrival of autumn each year. This tradition has a long history and has undergone various social, cultural, and political dynamics. However, in the contemporary context, the understanding and meaning of the moon cake tradition among the Chinese ethnic community in Bogor has shifted, especially between generations. Factors such as cultural localization, differences in beliefs, and a lack of intergenerational literacy regarding Chinese cultural traditions have influenced the continuity of this practice. This study aims to understand the contemporary development of the moon cake tradition through the perspective of traditional re-creation in the Chinese ethnic culture in Bogor. This study uses a qualitative approach with participatory observation and in-depth interviews. The conceptual framework used includes the concepts of traditional recreation, the moon cake tradition, and local Chinese ethnic identity. The results show that the moon cake tradition is still practiced routinely every year by the Chinese ethnic community in Bogor across generations. Practices include rituals to worship ancestors, eating moon cakes with family, and the tradition of exchanging cakes or gifts. The moon cake tradition is contemporarily interpreted as an effort to maintain family relationships, strengthen ethnic identity, and express gratitude and respect for ancestors in the context of cultural change.